Pengaruh IPO Terhadap Kinerja Keuangan, Good Corporate Governance dan Nilai Perusahaan Emiten Skala UKM di Bursa Efek Indonesia: IPO’s Effect on Financial Performance, Good Corporate Governance and Firm Value of SME Issuers in Indonesia Stock Exchange - Risa Resmita Dewi; Anny Ratnawati; Lukytawati Anggraeni (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The financial sector, especially the Indonesian capital market, shows a positive trend with an increase in the number of IPO companies each year. The contribution of national GDP and the number of SME companies in Indonesia are high, so development efforts to facilitate the provision of capital through the capital market are carried out by the government. Basically, IPO funding obtained by the company will provide an opportunity for the issuer in the hope of improving financial performance so that the company's valuation among investors increases and also improves corporate governance.Purpose: This study aims to analyze the influence of Initial Public Offerings on Financial Performance, Good Corporate Governance and Valuation in SME’s Issuer on Indonesia Stock Exchange. Design/methodology/approach: The research was conducted using the Mann-Whitney test and OLS multiple regression analysis. Findings/Result: The results showed that financial performance has a significant difference after IPO particularly on activity ratio and leverage ratio. It is known that the variables company such as size, outstanding shares, profitability ratio and dummy covid have an effect on company valuation. While leverage, income and activity ratio have no effect on company value. In addition, leverage, company size, outstanding shares and dummy covid have significant effect on good corporate governance.Conclusion: Issues from SME can be considered potential options for investors in the capital market. Besides that, it encourages other SME to obtain funding from the capital market.Originality/value (State of the art): This study examines opportunities for SME companies that can increase their business scale through the capital market by meeting the requirements of financial performance prospects and the implementation of good corporate governance so that they can increase the company's value. Keywords: financial performance, good corporate governance, IPO, firm value, SME